2018
DOI: 10.1073/pnas.1722295115
|View full text |Cite
|
Sign up to set email alerts
|

Circadian misalignment induces fatty acid metabolism gene profiles and compromises insulin sensitivity in human skeletal muscle

Abstract: SignificanceShift workers are affected by circadian misalignment and have an increased risk to develop metabolic diseases such as type 2 diabetes. Here, we show that during simulated short-term night shift work insulin sensitivity at the level of skeletal muscle is decreased in male volunteers, which could contribute to the development of type 2 diabetes in the long term. We also find that the muscle molecular clock does not align rapidly to the new behavioral cycle. Importantly, on the level of the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
138
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 31 publications
9
138
1
Order By: Relevance
“…The level of insulin is controlled by the circadian clock (35). Studies of animal mutants with circadian clock gene mutations and studies of shift workers have demonstrated that circadian misalignment leads to elevation of the insulin level (36,37). Consistently, 10-h light/dark schedule resulted in increased insulin levels and insulin:glucose ratios in mice (38).…”
Section: Discussionmentioning
confidence: 98%
“…The level of insulin is controlled by the circadian clock (35). Studies of animal mutants with circadian clock gene mutations and studies of shift workers have demonstrated that circadian misalignment leads to elevation of the insulin level (36,37). Consistently, 10-h light/dark schedule resulted in increased insulin levels and insulin:glucose ratios in mice (38).…”
Section: Discussionmentioning
confidence: 98%
“…Our interpretation of these data is based on the circadian clock orchestrating a switch between primarily carbohydrate oxidation to primarily lipid oxidation between the last meal of the day and the onset of circadian-timed sleep [1,3,6,7]. Instead of fasting between dinnertime and breakfast, if a person eats during the late evening, carbohydrates will be preferentially metabolized as sleep initiates, delaying the timing of the switch to primarily lipid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…These daily oscillations are controlled by the circadian clock, which is composed of an autoregulatory biochemical mechanism that is expressed in tissues throughout the body and is coordinated by a master pacemaker located in the suprachiasmatic nuclei of the brain (aka the SCN [1,4]). The circadian system globally controls gene expression patterns so that metabolic pathways are differentially regulated over the day, including switching between carbohydrate and lipid catabolism [1,3,[5][6][7][8][9]. Therefore, ingestion of the same food at different times of day could lead to differential metabolic outcomes, e.g., lipid oxidation vs. accumulation; however, whether this is true or not is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,57,145 On the other hand, organ-specific glucose uptake is rhythmic. 59,78,146 Indeed, under physiological conditions, glucose tolerance is higher in the morning than during the night hours, reflecting anticipation of the activity phase and food intake.…”
Section: Goes Wrong: Circadian Misalignments In Human Pathologiesmentioning
confidence: 99%